Regularized learning with flexible constraints - Hüllermeier, Eyke (In Proceddings IDA-03, 5th International Symposium on Intelligent Data Anaysis)

Pairwise preference learning and ranking - Fürnkranz, J.; Hüllermeier, Eyke (In Proceedings ECML-2003, 13 th European Conference on Machine Learning, Cavtat-Dubrovnik, Croatia)

Testing Containment of XPath Expressions in Order to Reduce the Data Transfer to Mobile Clients - Böttcher, Stefan; Steinmetz, Rita (Advances in Databases and Information Systems, 7th East European Conference, ADBIS 2003)

A DTD Graph Based XPath Query Subsumption Test - Böttcher, Stefan; Steinmetz, Rita (Database and XML Technologies, First International XML Database Symposium, XSym 2003)

A Subset Test for XPath Expressions under DTDs - Böttcher, Stefan; Steinmetz, Rita (20th British National Conference on Databases, BNCOD 20, Poster Papers)

3D interaktives Baukastensystem unter Verwendung von Augmented Reality Techniken - Schwerdtfeger, Bj{\; Goetz, F; Domik, Gitta

Instance-based collaborative filtering with fuzzy labels - Hüllermeier, Eyke (in Proceedings EUSFLAT-2003 3th International Conference on the European Society for Fuzzy Logic and Technology, Zittlau, Germany)

A note on quality measures for fuzzy association rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (in Proceedings IFSA-03 10th International Fuzzy Systems Association World Congress, Istanbul, Turkey)

Inducing fuzzy concepts through extended version space learning - Hüllermeier, Eyke (in Proceedings IFSA-03 10th International Fuzzy Systems Association World Congress, Istanbul, Turkey)

Rechtsbegriffe deutsch / englisch / französisch - Krimphove, Dieter

Possibilistic instance-based learning - Hüllermeier, Eyke (Artificial Intelligence)

Flexibility and case-based evaluation in querying: An Illustration in an experimental setting - De Calmès, M.; Dubois, D.; Hüllermeier, Eyke; Prade, H.; Sèdes, F. (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

On the representation of fuzzy rules in terms of crisp rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Information Sciences)

Sequential decision making in heuristic search - Hüllermeier, Eyke (Planning Based on Decision Theory (CISM Courses and Lectures No.472))

Possibilistic case-based decisions - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Connectionist Approaches in Economics and Management Sciences)

Mining implication-based fuzzy association rules in databases - Hüllermeier, Eyke; Beringer, J. (Intelligent Systems for information processing: From representation to applications)

Handbuch Unternehmensnachfolge Recht - Basel II und Rating - Finanzierung - Fallbeispiele

Experiences from Teaching Software Development in a Java Environment - Breu, Ruth; Hellebrand, Sybille; Welzl, Michael

Einsatzbarrieren fuer Produktkonfiguratoren in der Automatisierungstechnik - Ergebnisse einer empirischen Untersuchung - Szydlowski, M.; Greve-Ecker, I.; Trier, Matthias (Industrie Management Journal 1/2003)

Anforderungen an die IT-Unterstuetzung für Communities of Practice im Unternehmen (in German) - Trier, Matthias (Industrie Management Journal)

Der 'Short-Clip' als Ansatz zur Produktion von video-basiertem E-Learning Content bei der VGU (in German) - Trier, Matthias; Herzog, Michael; Krallmann, Hermann (Proceedings Wirtschaftsinformatik 2003)

Integrating Communities of Practice with e-learning platforms to improve on-the-job-learning - Trier, Matthias (Proceedings of Organizational Knowledge, Learning and Capabilities Conference OKLC 2003, Barcelona, 13. April 2003.)
In knowledge intense business processes, a complex and dynamic body of knowledge is being built bottom-up by experience learning during exception handling and problem solving. Traditional qualification programs do not very effectively provide the special skills required. Communities of Practice are better supporting this dynamic on-the-job learning across hierarchies. Still, CoP approaches and platforms in many organisations can be improved by enriching them with e-learning components to create a connection between the unstructured personalisation strategy of CoPs and the structured training materials. Similarly, e-learning benefits from being linked to communities. In the article, the connections of both areas are analysed to derive a framework for integration. It proposes an agenda of activities for the two domains people-oriented and content-oriented integration of community management and e- learning. These two aspects affect the handling, configuration and design of software features. In a first stage, the challenge is mainly a management and organisational task. Consecutively, the integration processes can be further assessed in order to identify potentials for IT-automatisation.

IT-unterstuetztes Management virtueller Communities of Practice (in German) - Trier, Matthias (Proceedings DoIT Congress 2003, 24.11.2003)

Prototype implementation and performance evaluation of a QoS-conditionalized handoff scheme for mobile IPv6 networks - Neumann, Axel; Fu, Xiaoming; Karl, Holger (Computer Communications, 2003. CCW 2003. Proceedings. 2003 IEEE 18th Annual Workshop on)

Channel-Aware Schedulers For Voip And Mpeg4 For Wireless Communications - Aguiar, Ana Cristina Costa; Hoene, Christian; Klaue, Jirka; Karl, Holger; Miesmer, Horst; Wolisz, Adam (Proc. of 8th Intl. Workshop on Mobile Multimedia Communications (MoMuC'03))

Online scheduling for block-partitioned reconfigurable devices - Walder, Herbert; Platzner, Marco (Proceedings Design, Automation and Test in Europe Conference (DATE))

Fast online task placement on FPGAs: free space partitioning and 2D-hashing - Walder, Herbert; Steiger, Christoph; Platzner, Marco (Proceedings International Parallel and Distributed Processing Symposium)

Reconfigurable Hardware Operating Systems: From Design Concepts to Realizations - Walder, Herbert; Platzner, Marco (Proceedings of the 3rd International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Heuristics for Online Scheduling Real-Time Tasks to Partially Reconfigurable Devices - Steiger, Christoph; Walder, Herbert; Platzner, Marco (Proceedings of the 13th International Conference on Field Programmable Logic and Applications (FPL))

Online scheduling and placement of real-time tasks to partially reconfigurable devices - Steiger, Christoph; Walder, Herbert; Platzner, Marco; Thiele, Lothar (Proceedings 24th IEEE International Real-Time Systems Symposium (RTSS))

Many-body and overlayer effects on surface optical properties - Bechstedt, F.; Del Sole, R.; Glutsch, S.; Hahn, P. H.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (b))

Gallium-rich reconstructions on GaAs(001) - Pristovsek, M.; Tsukamoto, S.; Ohtake, A.; Koguchi, N.; Orr, B. G.; Schmidt, Wolf Gero; Bernholc, J. (physica status solidi (b))

Cycloaddition reaction versus dimer cleavage at theSi(001):C5H8interface - Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

Layer-by-layer analysis of surface reflectance anisotropy in semiconductors - Castillo, C.; Mendoza, Bernardo S.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Nanowire-induced optical anisotropy of the Si(111)-In surface - Wang, Shuchun; Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

P-richGaP(001)(2×1)/(2×2)surface: A hydrogen-adsorbate structure determined from first-principles calculations - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F.; Pulci, O.; Del Sole, R. (Physical Review B)

Pyrrole (C4H4NH) and Polypyrrole Functionalized Silicon Surfaces Calculated from First Principles - Schmidt, Wolf Gero; Seino, K. (Surface Review and Letters)
The functionalization of the Si(001) surface by pyrrole and polypyrrole is investigated by means of first-principles pseudopotential calculations. We find dissociative reactions, leading to the partial fragmentation of the molecule, to be energetically most favored for pyrrole adsorption. The lowest-energy configuration for monolayer coverage is characterized by pyrrole rings bonded to the surface via Si–N linkage. In coexistence with adsorption geometries where both N and C are bonded to the surface, this structure accounts very well for the available experimental data. Chemisorption of pyrrole is found to effectively passivate the Si(001) surface, irrespective of the details of the adsorption geometry. The formation of well-ordered polypyrrole structures on Si(001) may require chemical modifications of the polypyrrole chains in order to account for the lattice mismatch.

Surface Ordering of P-rich InP(001): Hydrogen Stabilization vs Electron Correlation - Hahn, P. H.; Schmidt, Wolf Gero (Surface Review and Letters)
The influence of hydrogen on the reconstruction of InP(001) surfaces is studied by first-principles calculations. One-monolayer phosphorus forming oppositely buckled dimers with one hydrogen adsorbed per dimer is energetically favored for a wide range of surface preparation conditions. The electronic structure and STM image calculated for this adsorbate geometry agree well with the experimental findings obtained after annealing of MOVPE-grown InP samples. The Si(001)-like surface ordering as well as the surface band gap of more than 1 eV, supposedly arising from electron correlation effects [Li et al., Phys. Rev. Lett.82, 1879 (1999)], are naturally explained by the hydrogen-stabilized surface structure favored by the total-energy calculations.

Chemisorption of pyrrole (C4H4NH) on Si(001) calculated from first-principles - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Surface Science)

Uracil Adsorbed on Si(001): Structure and Energetics - Seino, K.; Schmidt, Wolf Gero; Preuss, M.; Bechstedt, F. (The Journal of Physical Chemistry B)

InP(001)-(2×1) Surface: A Hydrogen Stabilized Structure - Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F.; Esser, N.; Vogt, P.; Wange, A.; Richter, W. (Physical Review Letters)

EfficientO(N2)method to solve the Bethe-Salpeter equation - Schmidt, Wolf Gero; Glutsch, S.; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Chemisorption of pyrrole and polypyrrole on Si(001) - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Physical Review B)

Heidegger interprete del trascendentale - Ficara, Elena (Giornale Critico della Filosofia Italiana)

Logik als Organon: Erfindung des Neuen und Beherrschung der Komplexität in den Wissenschaften - Peckhaus, Volker (expressis verbis. Philosophische Betrachtungen. Festschrift für Günter Schenk zum fünfundsechzigsten Geburtstag)

Jean Nicod (1893–1924). Note biographique, Übersetzung von Max Kistler, Institut Nicod, Paris - Peckhaus, Volker
http://www.institutnicod.org/jn.htm (25.11.2003, am 24.08.2020 nicht mehr vorhanden)

The Pragmatism of Hilbert’s Programme - Peckhaus, Volker (Synthese (special issue “History of Logic”, ed. Juliette Kennedy/Gabriel Sandu))
Rezension: MR 2005b:03021 (E. Mendelson).

Novel Modulation Schemes Minimizing the Switching Losses of Sparse Matrix Converters - Schafmeister, Frank; Kolar, Johann (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Evaluation of 1200V-Si-IGBTs and 1300V-SiC-JFETs for Application in Three-Phase Very Sparse Matrix AC-AC Converter Systems - Schafmeister, Frank; Herold, Simon; Kolar, Johann (Proc. 18th IEEE Applied Power Electronics Conf. (APEC))

Analytically Closed Calculation of the Conduction Losses of Three-Phase AC-AC Sparse Matrix Converters - Schafmeister, Frank; Baumann, Martina; Kolar, Johann (EPE Journal)